Nickel Metal Hydride Batteries (MDPI - Multidisciplinary Digital Publishing Institute, 2016)
This book contains twenty papers focusing on research investigations in the field of nickel/metal hydride (Ni/MH) batteries in 2016. These papers summarize the joint efforts in Ni/MH battery research from BASF, Wayne State University, the National Institute of Standards and Technology, Michigan State University, and FDK during 2015 and 2016 through reviews of basic operational concepts; previous academic publications; issued US Patents and filed Japan Patent Applications; descriptions of current research results in advanced components and cell constructions; and projections of future works.